Synthesis of α‐ and β‐Galactopyranose‐Configured Isomers of Cyclophellitol and Cyclophellitol Aziridine. Issue 27 (14th August 2014) - Willems, Lianne I.; Beenakker, Thomas J. M.; Murray, Benjamin; Gagestein, Berend; van den Elst, Hans; van Rijssel, Erwin R.; Codée, Jeroen D. C.; Kallemeijn, Wouter W.; Aerts, Johannes M. F. G.; van der Marel, Gijsbert A.; Overkleeft, Herman S.
Abstract: Cyclophellitol and cyclophellitol aziridine are potent and irreversible mechanism‐based inhibitors of retaining β‐glucosidases. Alterations in the configuration of these compounds can lead to irreversible inhibition of different classes of retaining glycosidases. We have recently reported on the design of a set of α‐galactopyranose‐configured cyclophellitol and cyclophellitol aziridine derivatives that inhibit human retaining α‐galactosidases. Moreover, we have shown that fluorescently labeled derivatives enable the activity‐based profiling of these enzymes in vitro. In this report we describe in detail the synthetic strategies that were used to obtain these epoxide‐ and aziridine‐based probes. In addition, we describe the parallel synthesis of a set of β‐galactopyranose‐configured cyclophellitol isomers as putative inhibitors of retaining β‐galactosidases. Abstract : The synthesis of α‐ and β‐galactopyranose‐configured derivatives of cyclophellitol and of cyclophellitol aziridine, either non‐tagged or functionalized with various reporter entities, is described. All epoxide‐ and aziridine‐based compounds are synthesized from a single cyclohexene precursor – (3 S, 4 S, 5 S, 6 R )‐3, 4‐dibenzyloxy‐5‐hydroxy‐6‐(hydroxymethyl)cyclohex‐1‐ene.